Should or could? Testing the use of autonomy-supportive language and the provision of choice in online computer-tailored alcohol reduction communication. (February 2019) - Altendorf, Maria B.; van Weert, Julia C.M.; Hoving, Ciska; Smit, Eline S.
Individuals can feel more motivated to change health behaviour when perceiving autonomy-support, as induced through non-pressuring message phrasing and the provision of choice: autonomy-supportive message framing. Additionally, controlling message phrasing – commands that do not provide choice – can thwart autonomy and lead to reactance, which is detrimental to the persuasiveness of health messages. Many health messages have not been formulated in an autonomy-supportive manner and therefore could arouse reactance, resulting in reduced intervention effectiveness. We aimed to test the effects of autonomy-supportive vs. controlling alcohol reduction message frames on individuals' perceived autonomy-support from these messages; and their reactance towards the message while considering the individual need for autonomy in the context of an online computer-tailored alcohol reduction intervention. A 2 (autonomy-supportive language vs. controlling language) × 2 (choice vs. no choice) between-subjects experiment ( N  = 521) was conducted using an online computer-tailored alcohol reduction intervention. Outcome measures were perceived autonomy-support and reactance and we investigated whether an individual's need for autonomy moderated the effect of autonomy-supportive and controlling message frames on those outcome variables. Multiple linear regression analyses showed that neither autonomy-supportive nor controlling message frames had significant effects on perceived autonomy-support or reactance, and there was no moderation from the need for autonomy. Overall, participants evaluated the intervention as positive and perceived high levels of autonomy-support, regardless of the message frame used. Future research needs to test whether the positive intervention evaluation is due to content tailoring, and whether more distinguishable manipulations of message frames could be effective.